2019
DOI: 10.1101/629493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide 5-hydroxymethylcytosine (5hmC) emerges at early stage of in vitro hepatocyte differentiation

Abstract: How cells reach different fates despite using the same DNA template, is a basic question linked to differential patterns of gene expression. Since 5-hydroxymethylcytosine (5hmC) emerged as an intermediate metabolite in active DNA demethylation, there have been increasing efforts to elucidate its function as a stable modification of the genome, including a role in establishing such tissue-specific patterns of expression. Recently we described TET1-mediated enrichment of 5hmC on the promoter region of the master… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…That being said, the study of epigenetics is still in its infancy. Recently we found that levels of 5hmC in gene bodies in differentiating hepatocytes is highly correlated with the expression of those genes [ 33 ]. Thus, there is still a lot more to discover regarding the function of modified bases.…”
Section: Discussionmentioning
confidence: 99%
“…That being said, the study of epigenetics is still in its infancy. Recently we found that levels of 5hmC in gene bodies in differentiating hepatocytes is highly correlated with the expression of those genes [ 33 ]. Thus, there is still a lot more to discover regarding the function of modified bases.…”
Section: Discussionmentioning
confidence: 99%